Embodied energy and cost of high temperature thermal energy storage systems for use with concentrated solar power plants. (15th October 2016) - Jacob, Rhys; Belusko, Martin; Inés Fernández, A.; Cabeza, Luisa F.; Saman, Wasim; Bruno, Frank
Highlights: Environmental impact and CAPEX of novel high temperature TES systems is presented. Three systems were studied; EPCM, PCM coil-in-tank and liquid sodium. The embodied energy and CAPEX are compared to other high temperature TES systems. The systems have energy payback periods of 1, 1.6 and 38.6 months, respectively. The EPCM system had the lowest CAPEX estimate of $11.2/kWht . Abstract: The intermittency of renewable energy systems remains one of the major hurdles preventing a large scale uptake of these technologies and concentrated solar power (CSP) systems are no different. However, CSP has the benefit of being able to store excess heat using thermal energy storage (TES). For the uptake of CSP with TES it must be demonstrated that the technology is both economically as well as environmentally feasible. This paper aims to investigate the economic and environmental impact of several TES options that are available for CSP systems. The investigated systems include an encapsulated phase change material (PCM) system, a coil-in-tank PCM system and a liquid sodium TES system. The economic impact in the current study refers to the capital cost (CAPEX) of each system including the tank, storage material, encapsulation cost (if applicable) and allowances for construction and engineering. The environmental impact of each system is accounted by calculating the embodied energy of each of the system components. Each storage system will be required to store a comparable amount of energy so that reliable conclusions can be drawn. The results from this analysis conclude that the encapsulated PCM (EPCM) and coil-in-tank system represent an embodied energy of roughly one third of the corresponding state-of-the-art two-tank molten salt system. Furthermore, the EPCM and coil-in-tank systems result in CAPEX reductions of 50% and 25% over the current state-of-the-art two-tank molten salt system. The liquid sodium system was found to result in higher embodied energy and CAPEX than any previously studied TES system. Finally, the advantages and disadvantages of each system was discussed and compared to previous literature.